Preparation and In vitro Evaluation of Theophylline Loaded Gastroretentive Floating Tablets of METHOCEL K4M (Dhaka University Journal of Pharmaceutical Sciences, 2008)
This investigation describes the preparation and in vitro evaluation of gastroretentive floating tablets of theophylline. Hydrophilic polymer METHOCEL K4M was used for its gel forming and release controlling properties. Sodium bicarbonate and citric acid were incorporated as gas generating agents. The effects of soluble components (sodium bicarbonate and citric acid), gel forming agent (METHOCEL K4M) and dose variation on drug release profile and floating properties were investigated. It has been observed that in all cases increase of the amount of floating agent caused a decrease of the floating lag time. Increase of theophylline load showed an increase of the floating lag time, which was independent of floating agent content. The release mechanisms were explored and explained with zero order, first order, Higuchi, Korsmeyer and Hixon-Crowell equations. The release rate, extent and mechanisms were found to be governed by the content of polymer and floating agent. The content of active ingredient was also a vital factor in controlling drug release pattern. It was found that polymer content and amount of floating agent significantly affected the time required for 50% of drug release (T50%), percentage drug release after 8 hours, release rate constant, and diffusion exponent (n). Kinetic modeling of dissolution profiles revealed that the drug release mechanism could range from diffusion controlled to case II transport, which was mainly dependent on presence of relative amount of theophylline, polymer and floating agent. Key words: Gastroretention, Floating tablet, Theophylline Â DOI = 10.3329/dujps.v7i1.1220 Dhaka Univ. J. Pharm. Sci. 7(1): 65-70, 2008 (June)